Anatomy of the bacitracin resistance network in Bacillus subtilis. Issue 4 (10th March 2016) - Radeck, Jara; Gebhard, Susanne; Orchard, Peter Shevlin; Kirchner, Marion; Bauer, Stephanie; Mascher, Thorsten; Fritz, Georg
Summary: Protection against antimicrobial peptides (AMPs) often involves the parallel production of multiple, well‐characterized resistance determinants. So far, little is known about how these resistance modules interact and how they jointly protect the cell. Here, we studied the interdependence between different layers of the envelope stress response of Bacillus subtilis when challenged with the lipid II cycle‐inhibiting AMP bacitracin. The underlying regulatory network orchestrates the production of the ABC transporter BceAB, the UPP phosphatase BcrC and the phage‐shock proteins LiaIH. Our systems‐level analysis reveals a clear hierarchy, allowing us to discriminate between primary (BceAB) and secondary (BcrC and LiaIH) layers of bacitracin resistance. Deleting the primary layer provokes an enhanced induction of the secondary layer to partially compensate for this loss. This study reveals a direct role of LiaIH in bacitracin resistance, provides novel insights into the feedback regulation of the Lia system, and demonstrates a pivotal role of BcrC in maintaining cell wall homeostasis. The compensatory regulation within the bacitracin network can also explain how gene expression noise propagates between resistance layers. We suggest that this active redundancy in the bacitracin resistance network of B. subtilis is a general principle to be found in many bacterial antibiotic resistance networks. Abstract : The bacitracin resistance network of Bacillus subtilis consists of two interdependent lines of defense. The primary, drug‐sensing layer of resistance is provided by the bacitracin‐specific ABC transporter BceAB. Its activity directly influences the response behavior of the secondary, damage sensing layer (BcrC, LiaIH). The observed compensatory regulation between these two layers results in an active redundancy within the bacitracin resistance network that can also be found in other antibiotic resistance networks.